Research on the method of skateboard edge grinding by combination of robot and pneumatic constant force grinding device. Issue 1 (July 2021) - Yao, Maoyun; Zheng, Changwan; Wang, Zihao; Qian, Jiangzhong; Xi, Qiang; Kuang, Shaolong
Abstract: The paper presents a method of robot skateboard edging grinding based on pneumatic constant force device. To solve the problem of modeling and complex algorithm of robot end active compliance control during the grinding process, a hybrid position/force control is proposed by controlling position and force separately. That is, a kind of 2 degrees of freedom pneumatic constant force grinding device is designed to realize the constant force control in the horizontal and vertical directions, while a robot is used only for position control. Then a fuzzy PID control algorithm is proposed for smooth grinding based on the dynamic modeling of the grinding device. Experiments show that the use of fuzzy PID can effectively improve the dynamic adjustment performance of the pneumatic constant force grinding system and reduce the steady-state error. Compared with normal PID, fuzzy PID reduces the step response adjustment time of the grinding system from 400ms to within 200ms. In addition, when the constant force control is disturbed, the response adjustment time is less than 100ms and there is no oscillation, and the standard deviation of the grinding force is within 1N, which has good robustness and fulfills the requirements of edging control.